Kebijakan Tindakan Praktik Kedokteran Gigi Selama Wabah Covid-19: Tinjauan Pencegahan Global - Verona Aulia Ditama Putra; Aulia Nur Kasiwi (Journal of Government Insight, 2021)
The paper aim to examine how dental policy across the world could confront health regulators worldwide in the face of outbreaks and financial constraints faced by dentists worldwide. Globally, current dental practice is limited to providing only emergency treatments. This move is appreciative, but has resulted in enormous financial losses worldwide sustained by dental care providers (DCPs). This research are using qualitative analysis that are gathering the data using perish and publish, and collecting the data through scopus database as the main sources in this research. In advance of collecting the data, this research is analysis by Nvivo tools and Vosviewer to knowing the clustering values of dental policy and knowing the networking of spreading the virus in term of dental policy. The result show that the guideline and policy in each country, since every country has different values those are faced in their country especially talking with Asian Country. As regards the contagious nature of COVID-19, an appropriate standard procedure policy for patient management and a recommendation for dental treatment in hospitals during the pandemic are imperative for some institutions. Dental treatment requires close proximity, face-to-face practices, and may produce droplets or aerosols containing water, saliva, blood, any other microorganisms and other debris during the procedure.